Breast-conserving Surgery Rates in Breast Cancer Patients With Different Molecular Subtypes: An Observational Study Based on Surveillance, Epidemiology, and End Results (SEER) Database. Issue 8 (February 2016) - Chen, Kai; Li, Shunrong; Li, Qian; Zhu, Liling; Liu, Yujie; Song, Erwei; Su, Fengxi
Abstract : Abstract: This study used the Surveillance, Epidemiology, and End Results database to compare breast-conserving surgery (BCS) rates across patients with different molecular subtypes. We identified female breast cancer patients who were diagnosed between 2010 and 2012 using the Surveillance, Epidemiology, and End Results database. Patients without available critical clinicopathological information were excluded. The chi-square test and logistic regression analysis were used to investigate factors associated with BCS. This study identified 85, 415 T1–2N0–3M0 breast cancer patients. Among the patients with HR+/HER2−, HR+/HER2+, HR−/HER2+, and HR−/HER2− diseases, 63.5% (38, 823/61, 142), 51.2% (4850/9473), 43.2% (1740/4030), and 55.7% (6000/10, 770), respectively, received BCS ( P < 0.01). Patients with HR−/HER2+ (odds ratio 0.58; 95% confidence interval, 0.54–0.62) disease were significantly less likely to receive BCS than patients with HR+/HER2− disease after adjustment for T-stage, N-stage, age, tumor grade, county type, and race. Differences in BCS rates between the HR+/HER2− and HR−/HER2+ subgroups were 29.1%, 14.0%, 10.1%, 8.5%, and 0.2% in patients with tumor sizes <10 mm, 10 to 20 mm, 20 to 30 mm, 30 to 40 mm, and 40 to 50 mm, respectively. Differences in BCS rates between the HR+/HER2− and HR−/HER2+ subgroups were 20.3% and 5.7% in node-negative and node-positive patients, respectively. BCS rates in patients with grades I, II, and III tumors in the HR+/HER2− and HR−/HER2+ subgroups were 72.2% and 34.6%, 62.7% and 42.3%, and 54.7% and 43.4%, respectively. Our study demonstrated that BCS rates varied significantly across molecular subtypes, especially in patients with lower tumor burden. HR+/HER2− and HR−/HER2+ patients exhibited the highest and lowest BCS rates, respectively. Abstract : Supplemental Digital Content is available in the text